Photogrammetric analysis of facial soft tissue profile of Iraqi adults sample with Class I normal occlusion: (A cross sectional study) - Suhaib M Al-Janabi; Fakhri A Ali (College of Dentistry/ University of Baghdad, 2014)
Background: The purposes of this study were to determine the photogrammetric soft tissue facial profile measurements for Iraqi adults sample with class I normal occlusion using Standardized photographic techniques and to verify the existence of possible gender differences. Materials and methods: Eighty Iraqi adult subjects (40 males and 40 females) with an age ranged between 18-25 years having class I normal occlusion were chosen for this study. Each individual was subjected to clinical examination and digital standardized right side photographic records were taken in the natural head position which is mirror position which the patient looking straight into his eyes into the mirror mounted on the stand. The photographs were analyzed using AutoCAD program 2011 to measure the distances and angles used in the Soft Tissue Photogrammetric Analysis. Descriptive statistics was obtained for the measured variables for both genders and independent- samples t-test was performed to evaluate the genders difference. Results and conclusions: The results indicated that: males had greater facial heights and lengths as well as greater prominences. The mean values of all angular variables were higher in males than females except in the following angular measurements: nasofrontal, mentolabial, angle of the middle facial third; and angle of the head position, with larger male dimensions in all linear measurements of the facial, labial, nasal, and chin areas except Canuts nasal prominence in nasal area. The nasofrontal, vertical nasal, nasal dorsum, cervicomental, middle facial third and facial convexity angles showed statistically signi?cant gender differences, in which the male dimensions were larger than females while the nasolabial, the mentolabial, nasal, the inferior facial third, the head position and total facial convexity angles showed statistically non signi?cant gender differences.